Experiential learning applied to under-graduate training of physiotherapy students - A.M. Marais (South African Journal of Physiotherapy)
This article describes the experiential learning model applied to undergraduate training of physiotherapy students. The aim is to aid the development of a student’s ability towards analytical, critical-evaluating and creative thought processes, stimulating his/her independent judgement of scientific data. This is what the successful physiotherapist should aim for.